Sleep duration, sleep variability, and impairments of visual attention. Issue 6 (June 2020) - Barclay, Nicola L; Rowley, Susan; Robson, Anna; Akram, Umair; Myachykov, Andriy
Attentional networks are sensitive to sleep deprivation. However, variation in attentional performance as a function of normal sleep parameters is understudied. We examined whether attentional performance is influenced by (a) individual differences in sleep duration, (b) sleep duration variability, and/or (c) their interaction. A total of 57 healthy participants (61.4% female, Mage  = 32.37 years, SD  = 8.68) completed questionnaires, wore wrist actigraphy for 1 week, and subsequently completed the attention network test. Sleep duration and sleep duration variability did not predict orienting score, executive control score, or error rates. Sleep duration variability appeared to moderate the association between sleep duration with overall reaction time (β = –.34, t  = –2.13, p  = .04) and alerting scores (β = .43, t  = 2.94, p  = .01), though further inspection of the data suggested that these were spurious findings. Time of testing was a significant predictor of alerting score (β = .35, t  = 2.96, p  = .01), chronotype of orienting (β = .31, t  = 2.28, p  = .03), and age of overall reaction time (β = .35, t  = 2.70, p  = .01). Our results highlight the importance of examining the associations between variations in sleep–wake patterns and attentional networks in samples with greater variation in sleep, as well as the importance of rigorously teasing apart mechanisms of the sleep homeostat from those related to the circadian rhythm in studies examining cognition.